Potassium Sorbate Residue Levels and Persistence in Citrus Fruit as Detected by a Simple Colorimetric Method - Montesinos-Herrero, Clara; Smilanick, Joseph L.; Hurley, J. Michael; Palou, Lluís (2017)
A colorimetric method that employed extraction of the macerated fruit, followed by a reaction with 2-thiobarbituric acid, was used to quantify potassium sorbate residues in citrus fruit. A recovery of more than 90% in oranges and lemons was obtained. Potassium sorbate residues determined by this method and a standard high-performance liquid chromatography (HPLC) method were similar. Residues were proportionate to the potassium sorbate concentration in the treatment solution. In oranges stored at 15 degrees C, following the potassium sorbate treatments, residues declined initially rapidly and later more slowly, until residues stopped declining after 6 days. A brief double-dip rinse in tap water applied immediately after immersion of lemons in a 2% (wt/vol) potassium sorbate removed more than 90% of the potassium sorbate residue. The influence of high-pressure water washing (HPWW) on potassium sorbate residues in potassium-sorbate-treated fruit was determined. Potassium sorbate residues were more effectively reduced by rinsing oranges than lemons.